Artificial Intelligence in Hand Surgery: The Future is Upon Us - Bryan S. Crook, MD; Eoghan T. Hurley, MBBS, PhD; Marc J. Richard, MD; Suhail K. Mithani, MD; Tyler S. Pidgeon, MD (Journal of Hand Surgery Global Online)
In just the past few years, artificial intelligence (AI) has transformed from a potential disruptive force in health care to a technology being rapidly deployed across multiple fronts in orthopedic care. The growth in AI use and development has largely occurred as computing technology has improved in concert with the massive amounts of data generation made possible by electronic medical records. The resulting impact of these technologies, including machine learning algorithms and large language models, has yet to be fully realized, but has already begun improving patient care, offloading administrative burden, and disrupting clinical research. The purpose of this review is to highlight areas in which AI is poised to change the delivery of surgical care with respect to hand surgery.